Cross-sectional study of factors related to COVID-19 vaccination uptake among university healthcare students - Kondo, Akiko; Abuliezi, Renaguli; Ota, Erika; Oki, Tomomi; Naruse, Kazuko (Frontiers in Public Health, 2023)
Introduction: Healthcare students are more likely to become infected than other university students as they may encounter patients with COVID-19 during clinical training. Vaccination uptake is essential to prevent infection. This study explored factors related to COVID-19 vaccination uptake among healthcare students. Methods: This cross-sectional study conducted online surveys of undergraduate and graduate nursing and healthcare graduate students from four medical universities in the Tokyo Metropolitan Area of Japan. Data were collected from June to August 2022, when the fourth vaccination program was initiated. Results: Data from 1,169 students were analyzed (response rate = 37.3%). The mean age was 25.1 ± 7.6 years, and most were female (82.3%). Academic majors included nursing (68.0%), medicine (16.3%), dentistry (9.3%), and others (6.4%). Thirty students (2.6%) were not vaccinated, one student (0.1%) had received one vaccination, 997 (85.3%) had received three, and 27 (2.3%) had received four. The major reason for not being vaccinated was insufficient confirmation of its safety (n = 25). Students who had received at least one vaccination (n = 1139), 965 (84.7%) reported experiencing adverse side effects, the most frequent being pain at the injection site (76.2%), followed by fever (68.3%). In the logistic regression, a greater number of vaccinations (3–4 times) was associated with older age (odds ratio, OR = 1.53), working (OR = 1.67), and more frequent infection-preventive behaviors (OR = 1.05). Significantly fewer students were vaccinated at University B than at University A (OR = 0.46). Additionally, those majoring in subjects other than nursing (OR = 0.28), and students from non-Asian countries (OR = 0.30) were less likely to be vaccinated. Discussion: It is necessary to pay attention to and encourage the vaccination of students who engage in low levels of preventive behavior, students who are young, international, or unemployed, and those in non-healthcare professional majors.